Effect of hypothyroidism on glycemic control in type 2 diabetics - Golwalkar, Jayant K.; Gudge, Sachin (International Journal of Advances in Medicine, 2020)
Background: The major cause for complications of diabetes is hyperglycemia which can be prevent or reversing complications by using key effective blood sugar control and improving the life quality. Recognizing the link between thyroid disease and diabetes is important to guide clinicians in optimal management of both conditions. Therefore, the current study is undertaken to study the effects of thyroid disease on glycerin administration in patients with type 2 diabetes mellitus (DM). Methods: The present cross-sectional study was carried out in the Department of General Medicine, ARMCH and RC, Kumbhari during study period of two years. All patients with type 2 diabetics who met the inclusion and exclusion criteria during the study period were sampled for the present study. Baseline data were recorded, including medical history, family history, drug history, and personal history. Clinical data was collected by using pre-structured questionnaires. Results: In the present study, Euthyroid was 84%, subclinical hypothyroidism was 12% and clinical hypothyroidism was 4%. Majority of the subjects belongs to age group of 51-60 years (36%). The association of hypothyroidism was found to be significant with glycated hemoglobin (HbA1c), duration of DM, electrocardiography (ECG) changes, retinopathy and nephropathy (p<0.0001). Conclusions: Early identification of thyroid dysfunction and correction of thyroid function may result in better glycerin control and help prevent the development of long-term complications.